Six Decades of Top Economics Publishing: Who and How? - Hamermesh, Daniel S (Journal of Economic Literature, 2013)
Presenting data on all full-length articles in the three top general economics journals for one year in each decade 1960s–2010s, I analyze changes in patterns of coauthorship, age structure and methodology, and their possible causes. The distribution of number of authors has shifted steadily rightward. In the last two decades, the fraction of older authors has almost quadrupled. Top journals are publishing many fewer papers that represent pure theory, regardless of subfield, somewhat less empirical work based on publicly available data sets, and many more empirical studies based on data collected by the author(s) or on laboratory or field experiments. (JEL A14)